A new paradigm to understand success in professional football: analysis of match statistics in LaLiga for 8 complete seasons. (4th July 2019) - Brito Souza, Diego; López-Del Campo, Roberto; Blanco-Pita, Hugo; Resta, Ricardo; Del Coso, Juan
ABSTRACT: The aim of this study was to identify match statistics that best explain the number of points obtained in a professional football league at the end of the season. To fulfill this aim, accumulated attacking and defensive match statistics along with the points earned at the end of each season were obtained from LaLiga (2010–2011 to 2017–2018). The analysis included a total of 3040 football matches. Bivariate correlation analysis shows that the number of shots (r = 0.42) and the number of corners (r = 0.42) were the attacking variables with the highest association to the number of points earned during the season. The defensive effectiveness against shooting conceded (r = −0.36) and the number of recoveries (r = 0.27) were the defensive variables with the highest association to the points earned during the season. A multiple regression analysis was able to explain 84.1% of the total variance in the number of points with attacking statistics and 73.5% with defensive statistics. In conclusion, shooting accuracy while attacking along with avoiding clear positions of shots from the opposing team during defensive plays are the indicators best associated with the points obtained at the end of the LaLiga championship.